Sistem Sosial dan Ekologi Pantai Batu Pinagut - Mosi, Yetty; Usman, Mutmainnah; Bempah, Irwan (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
The interaction of social-ecological systems in coastal villages often causes problems, ranging from decreasing ecological quality to social conflict. This research aims to determine the description of the social interaction system in the coastal area and to determine the description of the ecological system in the coastal area of Kuala Kaidipang Village, North Bolaang Mongondow Regency. The data used is secondary data obtained by direct observation. The research results show that the separation between social and ecosystem management causes a decline in small-scale fisheries production on the coast due to a decline in fish stocks. The decline in fish stocks is caused by overfishing, habitat degradation and pollution. Open access further exacerbates the problem of overfishing. Managers and stakeholders face difficulties in designing and implementing effective management solutions. As for social interaction, it can be seen from 2 aspects, namely close relations between residents, interaction with the natural environment and coastal activities. Meanwhile, the ecological system includes coastal ecological systems including marine biodiversity, mangrove ecosystems, human activities and sustainability.